The Pillars of the Will in Islamic Jurisprudence - Rohani, Mahbubullah; Rasekh, Habibrahman; Osuly, Abdulqudos (Integrated Journal for Research in Arts and Humanities, 2023)
Bequest (wasiyat) refers to a person's instructions regarding the distribution of their property after their death. It is a legitimate act that is emphasized by the Quran, Sunnah, consensus, and analogy. The ruling on bequest varies depending on the relationship between the testator and the beneficiary. It can be obligatory, recommended, disliked, or prohibited. It is not appropriate to appoint minors, insane persons, sinners, traitors, very old or infirm persons, or those who lack the necessary experience and maturity as executors. Entrusting guardianship to untrustworthy individuals is also not permissible, and if they betray the trust, they must be removed and compensated for any damage caused to the wards under their care. Familiar with the rights of detainees, including insane and mentally disabled individuals. The methodology employed in this research involves qualitative analysis focused on content from secondary data sources related to Islamic jurisprudence, particularly in the context of bequest and the appointment of executors. The data analysis process involves the categorization and classification of information derived from both primary and secondary sources. Ethical considerations form a critical component of this research. Adherence to Islamic ethical principles is maintained throughout the research process to ensure respect for religious sensitivities and the sanctity of Islamic teachings. This involves treating the data with the reverence it deserves within the context of Islamic jurisprudence. Sometimes the executor of a will is determined by the appointer, in which case they are called a "Mukhtar executor". A Mukhtar executor is someone who is appointed by the father or paternal grandfather of a child, an insane person, or mentally disabled individual to manage their financial affairs after their death. Sometimes, a judge appoints an executor known as a "Qadi executor" to manage the financial affairs of children. If appointed by the first executor, they are simply referred to as an executor. Will-making is a legitimate act that Islam emphasizes for the realization of the rights of minors. The ruling on making a will varies depending on the relationship between the testator and the beneficiary.